Eksitensi Pos Bantuan Hukum Dalam Menjamin Perlindungan Hak Perempuan Dan Anak Pasca Perceraian Studi Kasus Pengadilan Agama Makassar Klas 1 A. - Andi Agung Mallongi; Muh. Alghifari; Muhammad Rizal (USRAH: Jurnal Hukum Keluarga Islam, 2024)
This study aims to analyze the existence of Legal Aid Posts (Posbakum) at the Makassar Religious Court Class 1 A in ensuring the protection of women's and children's rights after divorce. Specifically, the study identifies the role of Posbakum in providing legal services related to women’s and children's rights such as alimony and child custody, as well as reviewing the effectiveness of Posbakum in drafting cumulative lawsuits, enabling the realization of fast, simple, and low-cost justice. This study also explores the challenges faced by Posbakum in carrying out its functions, particularly in divorce cases. The research method used is non-doctrinal (normative-empirical), where law is analyzed as an object linked to real-world conditions. This study examines legal provisions related to Posbakum and its implementation in society, with an applied research law approach, where applicable positive law is combined with the actual conditions in society. Research data sources are obtained from literature reviews, legal regulations, and direct interviews with Posbakum personnel at the Makassar Religious Court Class 1 A. The results of this discussion show that Posbakum plays a vital role in providing legal services to women and children after divorce but still faces various challenges. Some of these include limited budget, inadequate facilities, and low public awareness of the rights they can claim. The research results also indicate that other obstacles such as social stigma and low education levels affect the effectiveness of Posbakum services. Keywords: Divorce, Legal Aid Post, Makassar Religious Court Class 1 A ,Women's and Children's Rights,